076 Olympic-career related sports injury epidemiology: the retired olympian musculoskeletal health study (ROMHS). (3rd March 2020) - Palmer, Debbie; Cooper, Dale; Emery, Carolyn; Batt, Mark; Engebretsen, Lars; Scammell, Brigitte; Soligard, Torbjørn; Steffen, Kathrin; Whittaker, Jackie; Budgett, Richard
Abstract : Background: There are numerous studies describing elite athlete injury patterns seasonally and during major sporting events, however little is known about injury patterns during an elite athlete's entire sporting career. Objective: To describe Olympic-career related significant (≥30 days duration) injuries. Design: Cross-sectional survey. Setting: The survey was promoted and distributed in eight languages, worldwide via email and social media to Olympians who competed at a Summer and/or Winter Olympic Games and considered themselves retired from Olympic level training and competition. Patients (or Participants): 3, 357 Olympians (44% female), median age 44.7 yrs (16–97) from 131 countries and 57 Olympic Sports (42 summer, 15 winter), mean 1.6±0.9 Olympic Games per Olympian. Interventions (or assessment of risk factors): Olympic-career participation and significant injury history. Main outcome measurements: Injury prevalence by sport and anatomical region. Results: There were 3, 746 injuries reported in 2, 116 Olympians equating to 63.0% of Olympians (female 68.1%, male 59.2%; Summer 62.0%, Winter 69.0%) reporting at least one significant Olympic-career related injury. Overall, 1.1 significant injuries per Olympic-career were reported, with 63.8% (n=2389) of injuries occurring in training. By sport (Summer and Winter, respectively), injury prevalence was highest in handball (82.2%), badminton (78.4%) and judo (77.2%), and alpine skiing (82.4%), freestyle skiing (81.6%), and snowboarding (77.3%), and lowest for shooting (40.0%) and swimming (48.5%), and biathlon (40.0%) and curling (54.3%) (sports with n≥20 participants). The knee (20.6%), followed by the lumbar spine (13.1%), and shoulder (12.9%) were the most common affected injury locations. Conclusions: Overall, almost two thirds of Olympians reported sustaining at least one significant Olympic-career related injury. Similar to prospective injury studies, injury prevalence varied across sports, with the knee, lumbar spine and shoulder most commonly affected. It is important to understand the nature and causes of injuries during the entire career of an elite athlete, in order to better inform injury prevention and future athlete health initiatives.